Relation between Serum Ferritin and Iron Parameters with Preeclampsia - Robabeh Taheripanah; Parya Bustani Farkush (Tehran University of Medical Sciences, 2007)
Objective: Preeclampsia is one of the most important complications of pregnancy that is associated with increased morbidity and mortality. The aim of this study was to investigate the relation between serum iron status and ferritin with pre-eclampsia. Materials and Methods: This case control study evaluated 33 preeclamptic patients and 33 normal pregnant women before parturition in Imam Hossein hospital, from March 2003 till March 2004. Anemia, diabetes and multiple pregnancies were excluded from the study. Blood samples were taken before delivery and patients with HELLP syndrome were considered separately.  Data were analyzed using the SPSS software and P value <0.05 was considered statistically significant. T-test, chi-square and Fisher exact test were used. Results: The mean of serum iron level in case and control group was 79.9±32.4µg/dl and 88.6±40.8 µg/dl, respectively (NS). TIBC was 443.4±55.0 µmol/l and 383.7±63.6 µmol/l in normal patients and preeclamptics respectively (P = 0.002). Mean serum ferritin was 32.1±16.2 ng/dl in control group and 123.8±46.1 ng/dl in preeclamptics (P<0.001). No meaningful relation was observed between hematocrit, ferritin and iron. Conclusions: Ferritin increases and TIBC decreases in preeclampsia regardless of hepatic function. It seems that elevated serum ferritin (as an oxidative stress) can accelerate vascular damage. So, routine iron supplementation in preeclamptic women is questationable.